2021
DOI: 10.1039/d1cy01518d
|View full text |Cite
|
Sign up to set email alerts
|

Superior CNT-supported bimetallic RuCu catalyst for the highly selective hydrogenolysis of glycerol to 1,2-propanediol

Abstract: Selective hydrogenation of glycerol to 1,2-propanediol (1,2-PD) is a promising route for sustainable production of platform chemicals. Herein, a bimetallic RuCu catalyst supported on multiwall carbon nanotubes (RuCu/MWCNT) is reported...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[218] The conversion was limited (18 %) but a remarkable 1,2-PD selectivity (93 %), at 473 K and 50 H 2 bar, was obtained. [218] Recently, Pd-Ru nanoparticles were supported on a series of metal oxides and zeolitic supports with the aim of understanding the correlation between the catalytic activity (conversion and 1,2-PD yield) and the support acidity. [219] It was observed that C 3 products (instead of C 2 and C 1 ) were favored at 20 bar H 2 and 438 K, using catalysts displaying a moderate density of strong acid sites (130 NH 3 μmol g À 1 on 230 NH 3 mmol g À 1 of total acidity) as in TiO 2 , giving 55 % GL conversion and 1,2-PD with 50 % selectivity.…”
Section: Rutheniummentioning
confidence: 95%
See 1 more Smart Citation
“…[218] The conversion was limited (18 %) but a remarkable 1,2-PD selectivity (93 %), at 473 K and 50 H 2 bar, was obtained. [218] Recently, Pd-Ru nanoparticles were supported on a series of metal oxides and zeolitic supports with the aim of understanding the correlation between the catalytic activity (conversion and 1,2-PD yield) and the support acidity. [219] It was observed that C 3 products (instead of C 2 and C 1 ) were favored at 20 bar H 2 and 438 K, using catalysts displaying a moderate density of strong acid sites (130 NH 3 μmol g À 1 on 230 NH 3 mmol g À 1 of total acidity) as in TiO 2 , giving 55 % GL conversion and 1,2-PD with 50 % selectivity.…”
Section: Rutheniummentioning
confidence: 95%
“…The addition of copper to Ru nanoparticles, dispersed on multiwall carbon nanotubes by wet impregnation, significantly affected the reducibility of the metallic species, promoting the C−O cleavage [218] . The conversion was limited (18 %) but a remarkable 1,2‐PD selectivity (93 %), at 473 K and 50 H 2 bar, was obtained [218] .…”
Section: Late Transition Metalsmentioning
confidence: 99%
“…In particular PG finds wide application in cosmetics, as monomer, anti‐freeze and food additive. Apart from a few exceptions, mainly heterogeneous catalysts are used for the hydrogenolysis of GLY to PG [10–13] . The employed catalysts are typically based on the noble metals Ru/Re, [14] Pd [15–16] and Pt [17–18] or the non‐noble metals Ni [19–20] and Cu [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from a few exceptions, mainly heterogeneous catalysts are used for the hydrogenolysis of GLY to PG. [10][11][12][13] The employed catalysts are typically based on the noble metals Ru/Re, [14] Pd [15][16] and Pt [17][18] or the non-noble metals Ni [19][20] and Cu. [21] Next to the metal catalyst, a basic or acidic co-catalyst is added to enable the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…3 Therefore, the development of new technologies to efficiently utilize “this waste” is highly desirable. Selective catalytic conversion of glycerol into more useful molecules, such as dihydroxyacetone (DHA), 4 lactic acids (LA), 5 propanediol (PD), 6 and alanine, 7 has attracted extensive attention from both academia and industry. Lactic acid, as one of the most attractive biomass-based platform molecules, is an important precursor for the synthesis of biodegradable polylactic acid (PLA).…”
Section: Introductionmentioning
confidence: 99%